IMPLEMENTASI MODEL PEMBELAJARAN RECIPROCAL LEARNING BERBASIS HYPNOTEACHING DALAM UPAYA MENINGKATKAN RASA PERCAYA DIRI SISWA PADA MATA PELAJARAN MATEMATIKA - Irham Habibi Harahap; Muda Sakti Raja Sihite; Lena Rosdiana Pangaribuan; Dwi Novita Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the implementation of the Reciprocal Learning model based on Hypnoteaching in improving students’ self-confidence in mathematics learning. The background of this research is the low level of students’ self-confidence in mathematics classes, which affects their active participation, mathematical communication skills, and learning outcomes. The Reciprocal Learning model emphasizes activities such as summarizing, questioning, clarifying, and predicting, while the Hypnoteaching approach optimizes positive suggestion, persuasive language, and the creation of a comfortable and conducive learning environment. This study employed a quantitative approach with a quasi-experimental design. The research subjects were secondary school students divided into experimental and control groups. The research instruments included a self-confidence questionnaire, observation sheets of student activities, and mathematics achievement tests. Data were analyzed using descriptive and inferential statistical tests to determine differences in self-confidence improvement between the two groups. The results indicate that the implementation of the Hypnoteaching-based Reciprocal Learning model significantly improves students’ self-confidence compared to conventional learning methods. The improvement is evident in students’ courage to express opinions, ability to ask questions, participation in discussions, and confidence in solving mathematical problems. Therefore, this model is effective as an innovative instructional strategy to enhance both affective and cognitive aspects of students in mathematics learning.